Pemanfaatan Teknologi Informasi dan Manajemen Perubahan pada Kegiatan Bisnis di Era Globalisasi - Oxy Hendro Prabowo; Alit Merthayasa; Nur Saebah (Syntax Idea)
The era of globalization has brought significant changes in the business world. Advances in information technology are one of the main factors that influence the way companies manage business. The purpose of this study is to analyze how the use of information technology and change management contribute to the success of business activities in the era of globalization. This research uses qualitative research methods. The data collection technique was carried out by literature study obtained from Google Schoolar and Elsevier. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and conclusion drawing. The results showed that the use of information technology in business activities, namely ecommerce, data analysis for decision making, the use of artificial intelligence (AI), digital marketing and social media, collaboration and digital communication. Meanwhile, the use of change management includes the implementation of new technology, mergers and acquisitions, and flexibility in the organization.